Using local content initiative to upscale Climate Smart Agriculture in Nigeria - Olalekan, Sipasi (Technical Centre for Agricultural and Rural Cooperation, 2019)
Sipasi Olalekan, CEO and founder of Protect Ozone Sustainable Livelihood Initiative, explains how they have developed a 50% water saving irrigation kit that can store up to 40 litres of water that can last for 1 week.